The Relationship between Knowledge Sharing Behavior and Innovative Work Behavior through Innovation Self-Efficacy as Mediator: English - Deviyanti Anggini Putri; Arum Etikariena (Penerbit Goodwood, 2022)
Purpose: This study focuses on the role of innovation self-efficacy as a mediator in the relationship between knowledge sharing behavior and innovative work behavior. Research methodology: This research was conducted on 306 students from 14 faculties who were taking second to last semester. This study was measured using the Innovative Work Behavior (IWB) scale developed by (Janssen, 2000) Knowledge Sharing Behavior (KSB) developed by (Chen, Chen, & Kinshuk, 2009), and Innovation Self-Efficacy (ISE.6) developed by (Dungs, Sheppard, & Chen, 2017) The sampling method in this study used non-probability sampling with a convenience sampling technique. The statistical analysis technique used PROCESS through IBM SPSS version 21. Results: The results showed that innovation self-efficacy had a partial mediating effect on the relationship between knowledge sharing behavior and innovative work behavior. Limitations: The limitation in this study is that the effect of mediation is still partial mediation so it is hoped that further research can examine other mediator variables that have a stronger influence. Contribution: This research contributes to institutions, companies, or governments to develop programs or activities that aim to improve an individual's innovative work behaviors.